NON-SURGICAL ELIMINATION OF INTUSSUSCEPTION IN CHILDREN WITH HYDROECHOСOLONOSCOPY - G. N. Rumyantseva; A. A. Yusufov; A. N. Kazakov; Yu. F. Brevdo; S. V. Trukhachev; V. V. Svetlov (Неотложная медицинская помощь)
ABSTRACT. The possibilities of ultrasonography in the diagnosis of intussusception in children and disinvagination by hydroechocolonoscopy have been studied. The study was conducted in 2014–2015 at the Children’s Regional hospital of Tver. The age of children varied from 3 months up to 12 years. The disease duration before admission was 3–63 hours. The X-ray study confirmed the intussusception in all patients. In all cases, mesenteric lymphadenitis was revealed. Of 28 children, disinvagination was sucsessfuly performed with an aid of hydroechocolonoscopy in 26 (92.8%) patients. In 2 cases (7.2%), we failed to eliminate intussusception and children underwent the surgery. Three patients had recurrence; re-elimination of intussusception with hydroechocolonoscopy was performed. No complications were observed after disinvagination. Conclusion: The use of ultrasound in the diagnosis and treatment of intussusception eliminates radiation exposure, and allows the cause of intussusceptions to be determined as well. Disinvagination with hydroechocolonoscopy is technically simple, highly effective and safe.